Analysis and optimization of elastic-plastic framing structures under complex constraints / Tamprios plastinės rėminės konstrukcijos optimizavimas kompleksinėmis apribojimų sąlygomis - Agnė Gervytė; Ela Jarmolajeva (Engineering Structures and Technologies, 2014)
The paper presents a mathematical model for bar cross-sectional optimization of steel structureunder strength, stiffness and stability constraints. The theory of mathematical programming of extremum energy principles has been used for developing the introduced model. Solving a non-linear mathematical problem is subject to the MatLab programming environment. Because of the existing relationship between elastic response values and the optimized parameters of the structure, the problem has been calculated iteratively. The calculation algorithm has been applied to a frame with a truss span. The framing structure has been discretized by finite bar elements. The minimum volume of the structure that has not reached full plastic collapse but its individual members have experienced plastic deformation has been designed. According to the obtained optimal project, standard tube profiles have been chosen.